How Urbanization Drives Socio-Spatial Conflicts in Coastal Land Reclamation? - Nur, Khilda; Butt, Andrew; Ho, Serene; Vahanvati, Mittul (Alanya Üniversitesi, 2024)
In many cities, coastal land reclamation (CLR) is viewed as essential due to the impacts of urbanisation and to address the challenges of land scarcity. However, these approaches often involve complex environmental concerns, technological challenges, and community conflict. This study aims to explore socio-spatial conflicts that occur across different levels of cities in Indonesia, considering their unique characteristics and differences in geography, population (homogeneous, mesogeneous, and heterogeneous), and city status (megapolitan and metropolitan). This research focuses on three cities in Indonesia that have proposed CLR solutions to urbanisation: Jakarta, Makassar, and Denpasar. Data were gathered through observations and a desktop literature review. These data were then qualitatively analyzed using the directed content analysis method with ATLAS.Ti software. The study underscores that political interests significantly influence discussions on land reclamation in heterogeneous cities. In contrast, mesogeneous cities are driven by economic and legal factors, while traditional customs and practices dominate homogeneous areas. Comprehending the issues surrounding reclamation will inform the priorities of government policies based on the area's context.